2016
DOI: 10.4236/ojbm.2016.43043
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Institutional Support in SMEs Marketing, and Growth—A Case Study of Retail SMEs in Ghana

Abstract: Small and Medium Enterprises (SMEs) are still hailed as the panacea of economic development of many countries, since they play a fundamental part of the economic fabric in developing a crucial role in furthering growth, innovation and prosperity. In the quest to achieve growth, SMEs unfortunately face severe challenges including the marketing of their products, which stem from unqualified employees in the marketing department, inadequate finance to undertake marketing research, go international, and to partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…That is because banks prefer to allocate their resources to large enterprises rather than to SMEs because large enterprises have a lower failure risk (Khan and Almoharby 2007;Al-Shanfari et al 2013, Al-Barwani, 2014Ennis 2015). Previous studies found SMEs face challenges pertaining to the marketing of their products due to unqualified employees in the marketing department, inadequate finance to undertake marketing research, or to go international, and to participate in trade fairs (Berry 2002;Osei et al 2016;Al Belushi and Bagum 2017). For SMEs to be successful they have to continuously increase their market share and target the right market towards company's products and service.…”
Section: Business Mangers Perception Of the Internal Barriersmentioning
confidence: 99%
“…That is because banks prefer to allocate their resources to large enterprises rather than to SMEs because large enterprises have a lower failure risk (Khan and Almoharby 2007;Al-Shanfari et al 2013, Al-Barwani, 2014Ennis 2015). Previous studies found SMEs face challenges pertaining to the marketing of their products due to unqualified employees in the marketing department, inadequate finance to undertake marketing research, or to go international, and to participate in trade fairs (Berry 2002;Osei et al 2016;Al Belushi and Bagum 2017). For SMEs to be successful they have to continuously increase their market share and target the right market towards company's products and service.…”
Section: Business Mangers Perception Of the Internal Barriersmentioning
confidence: 99%
“…It is also reiterated in the study of Osei, Shao, Forkuoh, and Osei, A. (2016), The Impact of Institutional Support in SMEs Marketing, and Growth.…”
Section: International Journal Of Research Studies In Management 35mentioning
confidence: 91%
“…The impact of GDP per capita on market selection has also been studied in the context of business cycles and economic growth. Osei et al (2016) found that higher GDP per capita is associated with increased profit and market share for small and medium-sized enterprises (SMEs), influencing their marketing strategies and growth prospects. Additionally, the level of GDP per capita is an important factor in identifying international market competition intensity, reflecting its influence on market dynamics and competitive landscapes (Zhang & Li, 2022).…”
Section: Economic Distancementioning
confidence: 99%